CREDIT AGREEMENTS FOR BANKS USING GUARANTEED LETTERS APPOINTMENT OF CIVIL SERVANTS - Titik Aminah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Credit agreement with the guarantee of the decree of civil servants and any factors that become obstacles in non-performing loans at PT. Regional Development Bank of Riau Kepri (Persero) Batam branch. The results showed that civil servants' decrees could be used as a legitimate guarantee in banking law. The principle of credit law, which is based on the fulfillment of the requirements and completeness of the identity data of prospective debtors, both the provision of a period for debt repayment and the last is the submission of guarantees for the appointment of civil servants, all of which must be original. Credit settlement with a guarantee letter of appointment of civil servants who are in trouble (stuck) is the first holding of deliberations with the debtor to meet the elements of good faith if the debtor mutation is requested or confirmed in advance to the office/ institution where the debtor works for the transfer of funds to the repayment of credit with the guarantee of the decree on the appointment of civil servants.